i have the equation below, for which i need to find b and c eventually , with e being the exponential 2(be6c – be4c) = be4c – be2c I'm really stuck on this... please help thanks
Follow Math Help Forum on Facebook and Google+
chose b=0? c can be anything? If you arent allowed the trivial solution try substituting $\displaystyle u=e^{2c}$
2(be^6c – be^4c) = be^4c – be^2c sorry, the original thread is meant to show powers, but it doesnt, hope this helps I'm meant to get to something in this format, but no idea how 2be^2c(e^c-1) = be^c(e^c-1)
View Tag Cloud